PENGAMALAN NILAI-NILAI SILA KEMANUSIAAN YANG ADIL DAN BERADAB DALAM KEHIDUPAN SEHARI-HARI PESERTA DIDIK SMA NEGERI 1 GOWA - Umar, Firman; Suyitno, Imam; Malloco, Mutmainnah Sirajuddin (Jurnal Tomalebbi, 2024)
This research aims to: (1) To find out the eight points in the practice of just and civilized human values that are practiced in the daily lives of students at SMA Negeri 1 Gowa, especially class XI MIPA 3. (2) To find out the supporting factors in the practice of values fair and civilized human values in the daily lives of class XI MIPA 3 students. Data collection techniques through observation, interviews and documentation. Data obtained from interviews with teachers and students. Checking the validity of the data uses data source triangulation techniques. The results of this research found that the practice of fair and civilized human values was well practiced by students such as; recognize and treat human beings according to their dignity, recognize equality of human rights and obligations without discrimination, have an attitude of mutual love, tolerance for each other, not be arbitrary towards others, uphold human values, like to carry out humanitarian activities and have the courage to defend truth. Fair and civilized human values are carried out through the implementation of teaching and learning activities in the classroom and outside the classroom, and the factors that support the implementation of just and civilized human values are teacher example, teaching/guidance methods and the school environment.